Experimental Demonstration of Focal Plane Array Beamforming in a Prototype Radiotelescope - Hayman, D.; Bird, T.; Esselle, K.; Hall, Peter (IEEE, 2010)
Focal plane arrays are being developed to provide dishes with a wide field of view for both the next generation of radiotelescopes and to retrofit existing large radiotelescopes. We describe a prototype radiotelescope, comprising a two dish interferometer with real-time digital beamformer that was built to study focal plane array systems. Two beamformer weightings were applied to the system: A normalized conjugate match and the maximum sensitivity (G/T). Both incorporate the uncorrelated noise from the receiver chains and the latter includes correlated noise from spillover and coupling in the array. A black box approach is taken where the assembled system is considered and the only accessible data is that typically available from an operational radiotelescope. This approach is particularly suitable for complex active antennas where there is insufficient knowledge of the system for beamformer weights to be set a priori. It also allows adaptation to changes such as electronic gain drift, partial failures and alterations in the environment.